CONCEPTUAL METAPHORS Of ’ECONOMIC CRISIS’ IN ENGLISH: A HISTORICAL COGNITIVE PERSPECTIVE - Shevchenko, Iryna (Armenian Folia Anglistika, 2021)
This article explores the role of metaphor in the conceptualization of economic crisis in English in terms of the sociohistorical – cognitive – linguistic interface. On the material of economic mass-media discourse of the 19th century “long depression”, the 20th century Great Depression and the 21st century Global Economic Crisis It reveals the concept historical variation and defines the vector of its development. It also develops the methodology of historical cognitive analysis and proves that being а part of human social-cultural practice cognition is of historical nature. I claim that in historical perspective conceptual metaphors vary in their source domains as the result of transformations of the concept structure. The vector of diachronic change of conceptual metaphors of economic crisis corresponds to cladogenesis, which is the process of evolutionary splitting based on branching.